The Relationship Between Family Anxiety Levels and Knowledge of Initial Patient Management in the Emergency Department - Fatimah Putri Az-Zahra Ahmad; Ani Retni; Pipin Yunus; Setiawan (Universitas Muhammadiyah Palu, 2026)
Family anxiety in the Emergency Department (ED) commonly occurs due to uncertainty regarding the patient’s condition and limited understanding of initial treatment procedures. This condition may influence the family’s ability to receive information and support patient care. This study aimed to analyze the relationship between family anxiety levels and knowledge of initial patient management in the Emergency Department of RSUD M.M. Dunda Limboto. A quantitative correlational study with a cross-sectional design was conducted involving 91 respondents selected through accidental sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS), while knowledge was assessed using a structured questionnaire on initial patient management. Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most respondents experienced mild anxiety (42.9%) and had low knowledge levels (36.3%). Statistical analysis revealed a significant relationship between family anxiety levels and knowledge of initial patient management (p = 0.000). These findings indicate that family anxiety is associated with their understanding of emergency care procedures. Strengthening health education and effective communication by healthcare professionals is necessary to reduce anxiety and improve family comprehension during emergency services.